Fusion zone geometries, cooling rates and solidification parameters during wire arc additive manufacturing. (December 2018) - Ou, W.; Mukherjee, T.; Knapp, G.L.; Wei, Y.; DebRoy, T.
Graphical abstract: Highlights: A mechanistic model of wire arc additive manufacturing is validated experimentally. 3D transient model considers mass addition, heat transfer, fluid flow and free surface. New results on cooling rates, solidification parameters, droplet impact & finger penetration. Effects of power, welding speed, wire diameter and feed rate are evaluated. Abstract: Structure, properties and serviceability of components made by wire arc additive manufacturing (WAAM) depend on the process parameters such as arc power, travel speed, wire diameter and wire feed rate. However, the selection of appropriate processing conditions to fabricate defect free and structurally sound components by trial and error is expensive and time consuming. Here we develop, test and utilize a three-dimensional heat transfer and fluid flow model of WAAM to calculate temperature and velocity fields, deposit shape and size, cooling rates and solidification parameters. The calculated fusion zone geometries and cooling rates for various arc power and travel speed and thermal cycles considering convective flow of molten metal agreed well with the corresponding experimental data for H13 tool steel deposits. It was found that convection is the main mechanism of heat transfer inside the molten pool. Faster travel speed enhanced the cooling rate but reduced the ratio of temperature gradient to solidification growth rate indicating increased instability of plane front solidification of components. Higher deposition rates could be achieved by increasing the heat input, using thicker wires and rapid wire feeding.